Constitutional Nephrin Deficiency in Conditionally Immortalized Human Podocytes Induced Epithelial-Mesenchymal Transition, Supported by β-Catenin/NF-kappa B Activation: A Consequence of Cell Junction Impairment? - Gian Marco Ghiggeri; Maddalena Gigante; Armando Di Donato (International Journal of Nephrology)
The kidney glomerular podocytes are the cellular target of many chronic nephropathies both determined and acquired genetically. Mutations that affected the expression and/or the function of nephrin, a key component of the slit-diaphragm, are often causes of these pathologies. Recent findings showed that murine podocytes could undergo epithelial-mesenchymal transformation (EMT), suggesting new hypotheses about the pathogenesis of glomerular fibrosis. Here, we show that also human podocytes can undergo EMT, but more importantly nephrin ablation itself can trigger this phenotypic transformation. In fact, a model of human podocyte with engineered nephrin deficiency constitutionally expressed high levels of α-SMA, vimentin, fibronectin, and other hallmarks of EMT. Since it is known that cell contact abrogation is one of the triggers of EMT, we reasoned that nephrin loss could account for such cell junction disruption and cause the EMT. Therefore, we demonstrated that also normal podocytes could spontaneously undergo EMT if grown in Ca2+-free medium, which is known to impair cell contacts. The analysis of the main intracellular signal transduction pathways evidenced some major anomalies consequent with the nephrin abrogation. The most intriguing was the activation of β-catenin pathway, which plays a critical role in podocyte ontogenesis as well as in the nephrin expression and EMT regulation. Also other important signaling proteins, like NF-κB, p53, and retinoblastoma protein (RB), showed important activity modifications. Interestingly, most of the above indicated signaling pathway alterations were again reproducible by cell junction rupture, induced by Ca2+ deprivation. Finally, immunofluorescence analysis on kidney sections of patients with NS of Finnish type confirmed the constitutive expression of α-SMA.